2
$\begingroup$

If $a$, $b$ anc $c$ are three positives such that $abc = 1$ then prove that $$\large \sum_{cyc}\dfrac{a}{a + b^4 + c^4} \le 1$$

Here's what I did.

$$\large \sum_{cyc}\dfrac{a}{a + b^4 + c^4}$$

$$\le \sum_{cyc}\dfrac{a(b^2 + c^2 + bc)}{(b^2c + c^2b + abc)^2} = \dfrac{1}{(a + b + c)^2}\sum_{cyc}\dfrac{ab^2 + ac^2 + 1}{(bc)^2} \le \dfrac{1}{9}\sum_{cyc}\left(\dfrac{a}{b^2} + \dfrac{a}{c^2} + a^2\right)$$

And this is where I gave up.

Thanks for reading this. Even more thanks if you can solve the problem.

(Oh wait, I did try again.)

$$\large \sum_{cyc}\dfrac{a}{a + b^4 + c^4}$$

$$= 3 - \sum_{cyc}\dfrac{b^4 + c^4}{a + b^4 + c^4} \le 3 - 4\sum_{cyc}\dfrac{a^4}{b + c + c^4 + 2a^4 + b^4} = 2\sum_{cyc}\dfrac{b + c + b^4 + c^4}{b + c + c^4 + 2a^4 + b^4} - 3$$

...and again...

$$\large \sum_{cyc}\dfrac{a}{a + b^4 + c^4}$$

$$= 3 - \sum_{cyc}\dfrac{b^4 + c^4}{a + b^4 + c^4} \le 3 - \dfrac{1}{2}\sum_{cyc}\dfrac{(b^2 + c^2)^2}{a + b^4 + c^4} = \sum_{cyc}\dfrac{2(a - bc) + (b^4 + c^4)}{a + b^4 + c^4}$$

$$\le \sum_{cyc}\dfrac{1}{2(a - bc) + (b^4 + c^4)}\dfrac{[2(a - bc) + (b^4 + c^4)]^2}{a + 2b^2c^2}$$

$$= \dfrac{1}{2}\sum_{cyc}\dfrac{(a - bc + b^4)^2 + (a - bc + c^4)^2}{[2(a - bc) + (b^4 + c^4)](a + 2b^2c^2)}$$

And I need help. I would be grateful if you could help with this problem.

$\endgroup$
4
$\begingroup$

We can use rearrangement inequality to obtain$$ b^4+c^4\ge b^3c+bc^3=bc(b^2+c^2)=\frac{b^2+c^2}a. $$ This implies $$\begin{align*} \sum_{cyc}\frac{a}{a+b^4+c^4}&\le\sum_{cyc}\frac{a}{a+\frac{b^2+c^2}a}\\&=\sum_{cyc}\frac{a^2}{a^2+b^2+c^2}\\&=\frac{\sum_{cyc}a^2}{a^2+b^2+c^2}\\&=1, \end{align*}$$ as desired.

$\endgroup$
2
$\begingroup$

Another way:

By C-S $$\sum_{cyc}\frac{a}{a+b^4+c^4}-1=\sum_{cyc}\frac{a(a^3+2)}{(a+b^4+c^4)(a^3+1+1)}-1\leq$$ $$\leq\sum_{cyc}\frac{a^4+2a}{(a^2+b^2+c^2)^2}-1 =-\frac{2\sum\limits_{cyc}(a^2b^2-a^2bc)}{(a^2+b^2+c^2)^2}=-\frac{\sum\limits_{cyc}c^2(a-b)^2}{(a^2+b^2+c^2)^2}\leq0.$$

$\endgroup$
  • 1
    $\begingroup$ Wonderful solution ! (+1) $\endgroup$ – Song Mar 21 at 7:10
  • $\begingroup$ @Song Thank you, but I think your solution is better. $\endgroup$ – Michael Rozenberg Mar 21 at 7:11
  • $\begingroup$ Thank you :-) But I'm pretty sure that your answer would have contained the accepted solution if I had not answered. $\endgroup$ – Song Mar 22 at 4:04

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.